Pengembangan Web Profile Untuk Organisasi Koperasi Wanita Pengusaha Indo-nesia (KOWAPI) Cabang Bengkayang - Noviyanti P; Santi Thomas; Fra Siskus Dian Arianto (STMIK Royal, 2023)
Abstract: KOWAPI is an organization dedicated to Indonesian Women Entrepreneurs. KOWAPI itself is an abbreviation of the Indonesian Women Entrepreneurs Cooperative. KOWAPI is under the auspices of INKOWAPI (Parent Cooperative of Indonesian Women Entrepreneurs). INKOWAPI members consist of PUSKOWAPI and KOWAPI. KOWAPI itself has spread in various regions, including Bengkayang Regency. The Bengkayang branch of the KOWAPI organization is new and its management was only inaugurated in July 2021 for the management period from 2021-2026. Because the Bengkayang branch of KOWAPI organizations is still new, there are still many who do not know what the activities and vision, and mission of this organization are. Based on the existing problems, the Bengkayang branch of the KOWAPI organization is deemed necessary to have a web profile that accommodates the organization, both history, vision, and mission, and what activities exist in the organization. This web profile management will be made using CMS WordPress. CMS WordPress is a platform that is quite easy to implement, especially for ordinary people. With this web profile, it can help the KOWAPI organization to be better known and there will be more opportunities for the community, especially women entrepreneurs, to be able to join the organization. Keywords: inkowapi; kowapi organization; web profile; wordpress; Abstrak: KOWAPI merupakan organisasi yang diperuntukkan bagi Wanita Pengusaha Indo-nesia. KOWAPI sendiri merupakan singkatan dari Koperasi Wanita Pengusaha Indonesia. KOWAPI dinaungi oleh INKOWAPI (Induk Koperasi Wanita Pengusaha Indonesia). Anggota INKOWAPI terdiri dari PUSKOWAPI dan KOWAPI. KOWAPI sendiri telah tersebar diberbagai daerah, diantaranya adalah Kabupaten Bengkayang. Organisasi KOWAPI cabang Bengkayang termasuk baru dan kepengurusannya baru dilantik pada Juli 2021 untuk periode kepengurusan dari 2021-2026. Karena organisasi KOWAPI cabang Bengkayang ini masih baru maka masih banyak yang belum mengetahui apa saja kegiatan dan visi misi dari organisasi ini. Berdasarkan permasalahan yang ada, organisasi KOWAPI cabang Bengkayang ini dirasa perlu untuk memiliki web profil yang menampung tentang organisasi tersebut, baik sejarah, visi misi, dan kegiatan apa saja yang ada pada organisasi tersebut. Pengelolaan web profil ini akan dibuat dengan menggunakan CMS Wordpress. CMS Wordpress merupakan sebuah platform yang cukup mudah untuk diimplementasikan terutama bagi masyarakat awam. Dengan ada web profil ini maka dapat membantu organisasi KOWAPI agar lebih dikenal dan semakin banyak pula kesempatan bagi masyarakat khususnya para pengusaha wanita untuk dapat bergabung dalam organisasi tersebut.Kata kunci: inkowapi; organisasi kowapi; web profil; wordpress